Microstructure and nanoscaled characterization of HVFA cement paste containing Nano-SiO2 and Nano-CaCO3 - Shaikh, Faiz; Supit, S.; Barbhuiya, Salim (American Society of Civil Engineers (ASCE), 2017)
This paper presents the effects of nano-SiO 2 and nano-CaCO 3 on the microstructure of high-volume fly ash (HVFA) cement paste. The microstructures of HVFA cement pastes containing 40 and 60% Class F fly ash were evaluated at 28 days using nanoindentation, X-ray diffraction (XRD), thermogravimetric (DTA/TGA), and mercury intrusion porosimetry (MIP) analyses. A reduction of calcium hydroxide (CH) was seen in XRD analysis of HVFA pastes containing nanoparticles. This observation was also confirmed in the DTA/TGA analysis. The nanoindentation results also showed the evidence of pozzolanic reaction in the HVFA pastes, where the addition of 2% nano-SiO 2 and 1% nano-CaCO 3 increased the volume fractions of high-density and low-density calcium silicate hydrate (C- S- H) gels and confirmed the ability of nanoparticles to reduce the porosity of HVFA pastes, which was consistent with the MIP analysis. The improved nanostructure and microstructure of HVFA pastes due to the addition of nano-SiO 2 and nano-CaCO 3 in this study show that high-strength and highly durable sustainable concrete can be produced with lower repair and maintenance requirements for the concrete structures.